Design Of 0.18-μm CMOS Mixer For Medradio Application - Abu Bakar, Mohamad Redzuan (Universiti Sains Malaysia, 2018)
This thesis introduces a component of the Radio Frequency transceiver called the mixer. The mixer is a critical component in the RF systems, as a result of its ability for frequency conversion. This passages focuses on the design analysis and simulation of active down-conversion mixer. This mixer is described by its important design properties which consist of conversion gain, linearity, noise figure, and port isolation. The topologies that are given in this passage range from the most commonly known mixer design, to implement the design methods that are utilized to build the mixer important design properties as the request of CMOS technology and the overall RF system rises. All mixer topologies were designed and simulated using TSMC 0.18 μm CMOS technology in Advanced Design Systems, a test system utilized particularly for RF designs. The design was able to produce the conversion gain about 12.86 dB and 12.85 dB at 401 MHz – 406 MHz respectively. The NFobtained in this topology was 11.2 dB at 401.7 MHz and started to go below 11.19 dB at 405.8 MHz. IP1db and IIP3 was also able to meet the design target specification. Finally, the power consumption is 6.17 Mw at a 1.8 V.